Communicative Expansion of Drama and its Sociality - Šatkauskienė, Nomeda (Sociologija. Mintis ir veiksmas, 2002)
The paper analyses the communicational aspects in drama and discusses the interaction between drama, theatre and society. The expansion of performance theory and theatre semiotics has changed the emphasís of dramatic theory since 1970’s toward new concepts of communication in drama. This article gives particular attention to the semiotics ideas of the relationship between drama and mis en scene and investigates the role of the audience in the context of contemporary drama and theatre studies. The traditional model of communication from Aristotle and Plato, was understand as a simple conveyance of information or as the objective transmission of contents from sender to receiver, creating the intersubjective relationship that are the foundation of society. Recent critical practice and investigations by theorists such as Patrice Pavis, Marco De Marinis, Anne Ubersfeld, Kleir Elam has led to the radically different ways of the communicational concepts. The starting point of research into theatrical communication was the French linguist Georges Mounin’s (1969) denial of its possibility. Thus the main task of the theatre semioticians was to find a Specific model of theatrical communication. M. De Marinis argued, that the complexity and multiplicity of codes guarantees that a certain degree of comprehension (and communication either) is always achieved in the theatre. Mise en scene P. Pavis defines not as the transformation of drama text into performance, but rather as their confrontation. The process of drama’s concretizations series from ’textual’ to ’receptive’ concretization) is always concemed with the social context and cultural conditions surrounding the audience. The changing social context permits infinite number of the same drama texts readings. Mis en scene can be understood as the “social practice”. Thus communication theory with the attitude toward sociology gives more open concept of drama. The task of the audience nowadays is not to look for the “true” meaning in dramatic performance, but to create his own meaning in the process of communication. It means, that the “manipulation power of drama” as the ground for traditional theatrical communication is rejected. The perceptual studies - the “pleasure” of reading and viewing, the deconstruction of meaning - gives new conceptions of communicational and social aspects of drama.